Marginal Aaccuracy of Ceromer Crowns and Effect of Relining on the Fitness - F. Gerami-Panah; S. Boushehri (Tehran University of Medical Sciences, 2004)
Statement of Problem: Targis restorations provide good esthetic and clinical success; however, improving marginal accuracy requires further investigations. Purpose: The aim of this was to study evaluate the effect of relining on the marginal accuracy of ceromer crowns. Material and Methods: One ivorine maxillary central incisor was prepared for Targis crown. 10 acrylic models were duplicated from ivorine teeth. The specimens were randomly divided in to two groups. In the first group Targis crowns were made according to manufacturer's instructions. In the second group (relined group) after construction of Targis crown they were relined by Targis base. All of the specimens were luted with resin cement, embedded in epoxy resin and sectioned buccollingually and mesiodistally. Marginal and internal gap were assessed by image analysis system. Results: The mean marginal opening in labial and lingual margin of Targis crowns were 37.14±6.2 and 35.7±6.2 and in relined group it was 72.1±11 and 56±12µm respectively. Statistical analysis showed significant difference between two groups (P< 0.05). Conclusion: Considering limitations of this study, marginal opening and internal adaptation of the Targis crowns were in acceptable range for clinical application, however relining didn't improve the fitness of crowns.